Mesoporous Silica Nanoparticle-Based Imaging Agents for Hepatocellular Carcinoma Detection - Peng, Xuqi; Lin, Gan; Zeng, Yun; Lei, Zhao; Liu, Gang (Frontiers in Bioengineering and Biotechnology, 2021)
Hepatocellular carcinoma (HCC) is characterized by poor prognosis and high mortality. The treatment of HCC is closely related to the stage, and the early-stage of HCC patients usually accompanies a more long-term survival rate after clinical treatment. Hence, there are critical needs to develop effective imaging agents with superior diagnostic precision for HCC detection at an early stage. Recently, mesoporous silica nanoparticles (MSNs) based imaging agents have gained extensive attentions in HCC detection, which can serve as a multifunctional nanoplatform with controllable size and facile surface functionalization. This perspective summarizes recent advances in MSNs based imaging agents for HCC detection by the incorporation of several clinical imaging modalities. Multi-modal imaging system has been developed for higher spatial resolution and sensitivity. Even though some limitations and challenges need to be overcome, we envision the development of novel MSNs based imaging agents will offer great potential applications in clinical HCC detection.